Investigation of silicon nitride ceramic based inks for robocasting - Lua, Jerome Zhi Qin (2018)
In this report, characterization studies were conducted with (a) varying volume concentration of silicon nitride based inks, (b) fixed weight concentration of silicon nitride with varying volume percentage of dispersant polyacrylic (PAA) and polethylenimine (PEI) respectively, (c) fixed weight concentration of silicon nitride with fixed volume percentage of dispersant with varying concentration of rheology modifier methylcellulose (MC). Observations on the porosity and densities of sintered samples were determined by scanning electron microscope, JSM-5600LV (Jeol) and Archimedes’ principle respectively. It was observable that as weight concentration of solid loading increased, density increased while porosity decreased. As volume concentration of dispersant increased, density increased while porosity decreased. Lastly, weight concentration of rheology modifier increased, density decreased while porosity increased. The viscosities of the silicon nitride based inks with respectively formulation were determined by a rheometer, Discovery Hybrid Rheometer, DHR2 (TA Instruments). It was observable that the silicon nitride based inks of various weight concentration and formulation with dispersants and rheology modifier exhibited shear thinning phenomenon. The following relationships were also established as a result. As weight concentration of solid loading increased, viscosity increased. The increased in volume concentration of dispersant resulted in a decreased in viscosity. Lastly, viscosity increased as the weight concentration of methylcellulose increased. In all cases, the effect of solid loading, dispersant and rheology modifier played a crucial role in formulating the robocasting ink was discussed in this report.